BUSINESS PLAN FOR BEAUTY CARE IN LAMPUNG METRO CITY - Kurniawan, Denny; Putri, Sastya (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2023)
This research is about the preparation of business planning intended to obtain the results of the study of opportunities in the development of Fazia Beauty business and can be used as a guideline for the manager in this case is the owner. The research methods used are qualitative descriptive analysis and quantitative analysis. Through this method of analysis is expected to obtain an overview of the business environment of sales of products such as beauty care and skincare products by studying the existing environmental conditions and performing mathematical simulation calculations to see the prospects of this business financially. The results show that business opportunities in the beauty sector are still profitable for entrepreneurs. Continuously improving the quality of services and products will make consumers feel satisfied with all their needs. Increased sales as well as efficiency and efficiency so that they can continue to earn increased net profits